44 Charles Street : A Novel - Steel, Danielle (London Bantam Press, 2011)
Owner of a struggling art gallery and newly separated from her boyfriend, Francesca Thayer does the math and then the unimaginable. She puts out an advertisement for boarders, and soon her Greenwich Village house becomes a whole new world.
Keywords: Boardinghouses -- Domestic Fiction